Achievement Error Differences of Students With Reading Versus Math Disorders. (February 2017) - Avitia, Maria; DeBiase, Emily; Pagirsky, Matthew; Root, Melissa M.; Howell, Meiko; Pan, Xingyu; Knupp, Tawnya; Liu, Xiaochen
The purpose of this study was to understand and compare the types of errors students with a specific learning disability in reading and/or writing (SLD-R/W) and those with a specific learning disability in math (SLD-M) made in the areas of reading, writing, language, and mathematics. Clinical samples were selected from the norming population of the Kaufman Test of Educational Achievement–Third Edition (KTEA-3) as well as matched controls. Although the authors expected to find overall differences between the groups in their area of difficulties, the study revealed that the two clinical samples were more similar than different. In particular, the SLD-M clinical group performed lower on some errors that were not related to their area of disability compared with the SLD-R/W group. Implications of the study show the importance of error analysis especially when creating goals for individual education plans. Although a student may have an SLD-R/W, he or she may still need support in certain mathematic areas, and vice versa.